The Participation of Alumni in Successful Endowment and Waqf Funds :A Study of Selected Higher Educational Institutions (HEIs) in Malaysia - Nurul Adilah Hasbullah; Asmak Ab Rahman (Universiti Sains Islam Malaysia, 2024)
The Journal of Muamalat and Islamic Finance Research, Volume 21 Issue 1 Page (1-15)